Application of image processing in determination of erosion area in vacuum contacts - Hariom Patidar, Dr. Sunil Kushwaha (Journal of Neonatal Surgery, 2025)
The efficacy and durability of vacuum switches are significantly affected by contact surface erosion during arc interruption. Nevertheless, the quantitative study of ablation regions remains inadequately investigated. This paper presents a technique based on image processing to assess the surface ablation area of vacuum interrupter contacts using four color models: RGB, HSV, HSL, and HSI. Employing LabVIEW tools, pictures of contact surfaces after arcing were analyzed using threshold segmentation, filtering, and enhancement methods to locate and quantify ablation zones. Experimental findings demonstrate that the RGB system ensures steady pixel distribution, but the HSV, HSL, and HSI models provide enhanced detail and less vulnerability to noise. Post-processing using Gaussian filtering and Laplacian improvement diminished the mean assessment error to around 2.45%, hence affirming the method's accuracy. This method establishes a dependable basis for measuring surface wear in vacuum switches and refining their design to extend service life.